2016
DOI: 10.1159/000452221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Antidepressants on Acetylcholine-Induced Contractions in Isolated Guinea Pig Urinary Bladder Smooth Muscle

Abstract: Background/Aims: To investigate the potential inhibitory effects of 18 clinically available antidepressants on acetylcholine (ACh)-induced contractions in guinea pig urinary bladder smooth muscle (UBSM) in order to predict whether they may induce voiding impairment. Methods: Concentration-response curves for ACh-induced contractions in guinea pig UBSM strips were obtained in the absence or presence of selected antidepressants. When inhibitory effects indicated competitive antagonism, pA2 values agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…We were unable to find prior literature on the binding properties of sertraline toward α 2 -AR. However, the concentration (10 -5 mol/L) of sertraline exhibiting this physiological effect in our study was beyond clinically achievable blood concentrations (the negative logarithm of blood concentration is 6.84-7.14) [7]. Therefore, the possibility that sertraline causes incremental urethral resistance-induced dysuria due to α 2 -AR antagonism is unlikely.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…We were unable to find prior literature on the binding properties of sertraline toward α 2 -AR. However, the concentration (10 -5 mol/L) of sertraline exhibiting this physiological effect in our study was beyond clinically achievable blood concentrations (the negative logarithm of blood concentration is 6.84-7.14) [7]. Therefore, the possibility that sertraline causes incremental urethral resistance-induced dysuria due to α 2 -AR antagonism is unlikely.…”
mentioning
confidence: 53%
“…6A, C). Clinically achievable blood concentrations, expressed as negative logarithms, range from 6.13-6.91 and 5.41-5.71 for mirtazapine and trazodone, respectively [7]. This information suggests that both mirtazapine and trazodone within their clinical ranges induce dysuria by increasing urethral resistance.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…After incubating for 30 min in the presence of an arbitrary antidepressant (10 −6 mol/L), NA (10 −8 ‐10 −4 mol/L) was again cumulatively applied to construct the third concentration‐response curve, which was compared with the second (control) concentration‐response curve. A concentration of 10 −6 mol/L was used for all antidepressants in this study, as this concentration was estimated to be achieved in the blood at clinical dose ranges …”
Section: Methodsmentioning
confidence: 99%
“…In addition to tricyclic antidepressants, it has been shown that maprotiline, a tetracyclic, and mirtazapine, a NaSSA, competitively inhibit ACh‐induced contraction at clinically used dose ranges. Thus, these antidepressants may cause anti‐cholinergic action‐derived urination disorders as well …”
Section: Introductionmentioning
confidence: 99%